THE EVOLUTION OF FLIGHT ELEMENTS IN COMPETITIVE UNEVEN BARS ROUTINES - José Ferreirinha; Joana Carvalho; Cristina Côrte-Real; António Silva (Science of Gymnastics Journal)
The purpose of this study was to evaluate and characterize external load trends related to flight elements in elite level uneven bars routines, based on analyses from 83 uneven bars routines from the world championships and the Olympic Games finals between 1989 and 2004. An observation category was constructed and validated, comprising eleven variables: number, difficulty, direct combinations of 2 and 3 flight elements, execution with straight or closed body configuration, preparatory elements, direction outwards or inwards to the low bar, and execution on the 1st or 2nd phase of the routine. Results showed a significant decrease in the number of preparatory elements, and the number of flight elements outwards from low bar and inwards to low bar significantly changed. With regards to the other observed variables we found no significant differences. Elite gymnasts usually perform 1 or 2 flight elements during uneven bars routines.. The difficulty of flight elements ranged from 1 to 2 D value flight elements in all cycles and gymnasts performed using predominantly closed body configurations. Based on the results it can be concluded that the number, direct combinations, and difficulty of the flight elements contradict what has been reported in the gymnastics literature, where a large increase of variables of external load in uneven bars routines was predicted.